The Concept of the Ideal Human in HAMKA's Thought: Toward a Reconstruction of Islamic Humanist Ethics - Rahmah Eka Saputri; Za'im Rais; Khoiriah Khoiriah (Ruhama : Islamic Education Journal, 2026)
This article examines the concept of the ideal human being (manusia utama) in  HAMKA’s thought as a formulation of Islamic humanistic ethics grounded in the integration of faith, reason, and moral virtue. The study is motivated by the contemporary humanitarian crisis characterized by moral degradation, materialism, individualism, and spiritual disorientation, which necessitates a reconstruction of Islamic thought capable of presenting an integral concept of the ideal human person. The research aims to analyze  HAMKA’s concept of the ideal human being, explain the ethical structure that shapes it, and explore its relevance in addressing contemporary human challenges. This study employs a qualitative library research method with a philosophical-analytical approach. Primary sources include  HAMKA’s major works, namely Falsafah Hidup, Tasawuf Modern, Lembaga Budi, and Tafsir al-Azhar, while secondary sources are drawn from relevant scholarly literature. The findings reveal that, in  HAMKA’s perspective, the ideal human being is not only spiritually pious but also possesses social and civilizational responsibility. Faith serves as the foundation of moral formation, while reason functions as an instrument of humanization that guides individuals toward wisdom. Furthermore, virtues such as iffah (self-restraint), ‘adalah (justice), syaja‘ah (courage), and hikmah (wisdom) constitute the ethical foundation that produces moral integrity. This study contributes to the development of Islamic philosophy and Islamic humanism by demonstrating that  HAMKA’s thought offers a religious-humanistic ethical paradigm that remains relevant in addressing the moral and spiritual crises of modern society.Keywords: HAMKA, ideal human being, Islamic humanism, Islamic ethics, morality